Regulation of Cell Types Within Testicular Organoids - Lara, Nathalia de Lima e Martins (Endocrinology, 2021)
Organoids are 3-dimensional (3D) structures grown in vitro that emulate the cytoarchitecture and functions of true organs. Therefore, testicular organoids arise as an important model for research on male reproductive biology. These organoids can be generated from different sources of testicular cells, but most studies to date have used immature primary cells for this purpose. The complexity of the mammalian testicular cytoarchitecture and regulation poses a challenge for working with testicular organoids, because, ideally, these 3D models should mimic the organization observed in vivo. In this review, we explore the characteristics of the most important cell types present in the testicular organoid models reported to date and discuss how different factors influence the regulation of these cells inside the organoids and their outcomes. Factors such as the developmental or maturational stage of the Sertoli cells, for example, influence organoid generation and structure, which affect the use of these 3D models for research. Spermatogonial stem cells have been a focus recently, especially in regard to male fertility preservation. The regulation of the spermatogonial stem cell niche inside testicular organoids is discussed in the present review, as this research area may be positively affected by recent progress in organoid generation and tissue engineering. Therefore, the testicular organoid approach is a very promising model for male reproductive biology research, but more studies and improvements are necessary to achieve its full potential.